FORMATION OF THE INVESTMENT CLIMATE OF UKRAINE AS A PREREQUISITE FOR ITS SUSTAINABLE SOCIAL AND ECONOMIC GROWTH (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The purpose of the article is to substantiate the scientific, methodological and practical aspects of the formation of a favorable investment climate in Ukraine as a prerequisite for its sustainable socio-economic growth, to assess the systemic factors influencing the development and perception of the domestic investment climate by business, and to identify key priorities for its improvement for national and foreign investors. The article analyzes the dynamics of foreign direct investment in Ukraine, the volume and structure of sources of financing for domestic capital investments, and assesses the need for investments for the post-war reconstruction of Ukraine. The systemic factors and conditions for the formation of a favorable investment climate in Ukraine as a prerequisite for its sustainable socio-economic growth are identified. The risks and barriers, investment priorities and business expectations regarding the improvement of the investment climate in Ukraine to promote national and foreign investments are substantiated. Despite the war, Ukraine's investment potential, according to experts' forecasts, remains significant. Domestic business in extremely difficult conditions is adapting, developing and actively seeking foreign partners for the recovery and growth of the Ukrainian economy. Important drivers of investment are Ukraine's course towards European integration, visa-free travel, preferences for international trade, deregulation and digitalization of public services, grant and blended financing from EU countries. The investment climate can be considered as an integral economic, political, social and psychological phenomenon, which is formed under the influence of a significant number of determinants, in particular, international, state-political, legislative, financial and economic, market, infrastructure, resource, socio-demographic, information, organizational, environmental, socio-cultural and other prerequisites that determine the investment potential, investment attractiveness, investment activity, investment risks and security of capital investment in the appropriate level of the economic system. The process of creating a favorable investment climate in Ukraine requires a systemic approach, taking into account the influence of exogenous and endogenous factors and conditions, systematic and unsystematic risks, strategic national guidelines, which will allow for the implementation of a targeted state policy to stimulate the inflow of foreign and domestic investments. This will allow identifying key areas for the effective use of capital investments at different levels of the economy: country, region, sector, industry, enterprise. It is important to identify key factors and conditions for the business environment's perception of the investment climate in Ukraine, which include investment risks and barriers, national investment priorities, and expectations of domestic and foreign investors regarding appropriate steps by the state to improve it.
Keywords: investment climate; investment potential; investment attractiveness; investment activity; investment security; socio-economic growth of Ukraine